CLINICAL ASSISTED REPRODUCTION: Development of Blastocyst-Stage Embryos After Round Spermatid Injection in Patients with Complete Spermiogenesis Failure - Vicdan, Kubilay (Kluwer Academic Publishers-Plenum Publishers, 2001)
Purpose: Our purpose was to evaluate the progression of embryos derived from round spermatid injection to the blastocyst stage and compare the results with those obtained by the use of testicular or epididymal spermatozoa. Methods: Thirty-eight patients with azoospermia enrolled in this study. In 29 patients with obstructive or nonobstructive azoospermia, spermatozoa were recovered from epididymis or testis. In the remaining nine cases with nonobstructive azoospermia, only round spermatids were found in seven, whereas in two of the patients, there were no elongated or round spermatids. Six of these cases underwent round spermatid injection. Results: Twenty-one of 29 patients with injection of spermatozoa underwent embryo transfer on day 3, and 10 pregnancies (47.6%) were obtained. In eight cycles, embryos were further cultured for delayed transfer. In six cases undergoing round spermatid injection, no transfer was performed on day 3 and extended culture with delayed embryo transfer was applied. The mean number of fertilized oocytes and mean number of embryos on day 3 and also the fertilization rate and mean number of good-quality embryos on day 3, mainly grade 1 or 2, were statistically significantly higher in the spermatozoa group than the round spermatid injection group. Compared to the spermatozoa group, the number of arrested embryos was significantly higher and the number of blastocyst-stage embryos and number of good-quality blastocysts were significantly lower in the spermatid injection group. No blastocysts developed in two spermatid cycles and embryo transfer was not possible, and in the remaining four cycles, after at least one blastocyst transfer, no pregnancies were achieved. However, in eight cycles with extended culture in the spermatozoa group, embryo transfers were achieved in all and three pregnancies, for a pregnancy rate of 37.5%, were obtained after blastocyst transfer. Conclusions: Our preliminary results showed that round spermatid injection was associated with a significantly lower fertilization and embryo development rate and a significantly higher developmental arrest rate compared with the injection of spermatozoa. Extended culture and delayed embryo transfer did not improve the clinical outcome after round spermatid injection, and these results suggested a developmental failure in embryos preventing successful implantation after round spermatid injection.